Strategic directions of sustainable development of the tourism industry - Tranchenko, L.; Yavorska, V.; Tereshchuk , N. (Journal of Education, Health and Sport, 2023)
Today, in the conditions of global restructuring and reorientation of economic sectors, the growth of people's needs and motives for tourism is important. Tourism as a branch of the economy is gradually taking leadership positions in many countries of the world, as well as in Ukraine in the future. Therefore, we have significant unrealized human, natural-resource, historical-cultural, tourist-recreational and scientific-technical potential, a good geographical location, and a favorable climate. Also, the peculiarity of the current situation in the country, economic and political instability, the conditions of the military conflict, insist on the further development of our state, which must necessarily include the creation of conditions for the development of the tourism industry. At the same time, the formation of a highly developed tourism industry and its integration into the world market of tourist services are connected with the need to solve acute socio-economic problems and attract international experience. The article reveals that the phenomenon of the 21st century. determine today - the hospitality industry, which has become one of the leading directions of socio-economic activity. It has been proven that this is the business of the 21st century. which contributes to the creation of new jobs, the search for methods of increasing the competitiveness of enterprises at the global level, the popularization of the country on the international market of services and, as a result, raising the level of the national economy. However, in recent years, the tourism industry in Ukraine has been in a state of stagnation, therefore, the determination of factors influencing the development of the hospitality industry is relevant, because with the help of the acquired knowledge, it is possible to prevent the degradation of one of the most promising branches of international business. The article examines the influence of factors on the sustainable development of the tourism industry, economic studies of the potential opportunities of this industry within the general strategy of the socio-economic development of the world in general and Ukraine in particular.